2011
DOI: 10.1002/syn.20957
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease: β‐amyloid plaque formation in human brain

Abstract: Although the precise cause of Alzheimer's disease is not known, the β-amyloid peptide chains of 40-42 amino acids are suspected to contribute to the disease. The β-amyloid precursor protein is found on many types of cell membranes, and the action of secretases (β and γ) on this precursor protein normally releases the β-amyloids at a high rate into the plasma and the cerebrospinal fluid. However, the concentrations of the β-amyloids in the plasma and the spinal fluid vary considerably between laboratories. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 85 publications
1
50
0
2
Order By: Relevance
“…A number of potential pathologies could be caused by nanoparticles, like that in respiratory, cardiovascular and gastrointestinal system [3]. Because of this problem, with the use of nanoparticles and growing funding for many researches of this type, a new discipline in science arose and that is nanotoxicology [15]. Also there is a lack of standardize protocols for testing their possible toxic impact on biologic systems [16].…”
Section: Photostimulation and Qdsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of potential pathologies could be caused by nanoparticles, like that in respiratory, cardiovascular and gastrointestinal system [3]. Because of this problem, with the use of nanoparticles and growing funding for many researches of this type, a new discipline in science arose and that is nanotoxicology [15]. Also there is a lack of standardize protocols for testing their possible toxic impact on biologic systems [16].…”
Section: Photostimulation and Qdsmentioning
confidence: 99%
“…Some studies have shown that the toxicity of the QDs is size and concentration related and that CdSe quantum dots are toxic and aren't suitable for medical purposes, but with the ZnS coating it was proven a significant decrease in toxicity in cell culture [15].…”
Section: Photostimulation and Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ es producto de la proteína precursora de amiloide (APP) que es clivada por proteasas (secretasas α, β, γ); el sitio de clivaje determinará el origen de varias isoformas de Aβ que tienen entre 36 y 43 aminoácidos. Investigaciones recientes han asociado la isoforma Aβ 42 en la formación de placas amiloideas 14 . Si bien son numerosos los mecanismos que definen a Aβ como el principal responsable de la muerte neuronal (activación de microglias, aumento de citoquinas neurotóxicas, daño oxidativo, etc.…”
Section: Descripción Molecularunclassified
“…NTF deficiency has the same presentation as the end-point of AD, neuronal loss and synaptic dysfunction. Regionalized neuronal death/loss and synaptic impairment in the process of AD have been demonstrated in many diagnostic, clinical, and pathological studies [56][57][58][59] . For example, West et al [60] found that neurons in the CA1 region of the hippocampus decline from 14.08 × 10 6 neurons in an age-matched control group to 4.40 × 10 6 neurons in an AD group.…”
Section: Aβ Downregulates Ntfsmentioning
confidence: 99%